Level of satisfaction to clinical learning environment and its associated factors among nursing students of public universities in Central Ethiopia. - Birhanu Tesfaye; Adamu Birhanu; Jiregna Darega; Samuel Abate Walda; Meseret Robi Tura (PLoS ONE)
Background Students' satisfaction with clinical learning environment is a vital to evaluate teaching-learning process. However, there is a scarcity of information regarding the nursing students' satisfaction with clinical learning environment and associated factors in Ethiopia. The purpose of this study was aimed to assess level of satisfaction to clinical learning environment and its associated factors among nursing students of public universities in Central Ethiopia, 2022. Méthodes An institution based cross-sectional study was conducted among 245 undergraduate nursing students found in Universities of central Ethiopia from September 1-30, 2022. A simple random sampling technique was applied to recruit study participants. Data were collected via pretested self-administered questionnaire. The data were entered into Epi data version 3.1 and exported to SPSS version 25 for analysis. Descriptive statistics like frequency, percentage, median and IQR were computed. Binary and multivariable logistic regression analysis was done. For measuring the strength of the association between the outcome and independent variables, adjusted odds ratios (AOR) along with 95% confidence interval (CI) was used. Finally, statistical significance was declared at p-value <0.05. Results In this study, nearly half of nursing students, 49% [95% CI (42.6-55.4)] were satisfied with clinical learning environment. Students who did met their clinical learning outcome [AOR = 2.742 (95%CI: 1.407-5.343)], Students those who met 3 times per week with clinical preceptors [AOR: 2.829 (95% CI: 1.428-5.602)] and students who perceived inadequate supporting staffs [(AOR: 0.136 (95%CI: (0.073-0.254)] were associated factors. Conclusion Meeting clinical learning outcome, students' perception of staff supports and having a frequent contact of supervisor were an association with satisfaction statistically.